A necessidade de proteção internacional do direito à liberdade de expressão na América Latina: um estudo da jurisprudência da corte interamericana de direitos humanos - Mendonça, Fernanda Graebin (2016)
The right to freedom of expression is a human right that, guaranteed by many international documents, such as the American Convention on Human Rights, is also considered a fundamental right by many States and the "cornerstone" of democracy. The complexity of freedom of expression is a reflection of the also complex societies, which establish connections in the form of networks in the private sector – by strengthening communications through new technologies such as the Internet – as in the public sector with the creation of international tribunals and human rights protection systems. However, even if this needed protection is internationally recognized, it is still possible to observe the occurrence of numerous violations of free speech, many of which take place in the American countries, especially those in Latin America that still face the remnants of government dictatorships in the twentieth century. Thus, violations of the right to freedom of expression – due to the new international context of protection of human rights – are not just concerns of States but also of international tribunals, such as the Inter-American Court of Human Rights, which vouched by their jurisdictions, it has a duty to recognize these violations in their decisions and make the States responsible for their acts. Given this, the present work has the main objective to verify if the Inter-American Court gives prevalence and special protection of the right to freedom of expression, recognizing violations of this right caused by the States. Therefore, the methodology used is the phenomenology, making use of a hermeneutic aspect. In addition, it is used the historical and monographic methods. The monographic method is employed in the form of a study of the case law of the Court, more specifically of four cases sentences selected by scientific criteria appropriate to the work proposal. About the procedures it was adopted the bibliographic and the case law (documents) analysis mainly. With regard to technique, record papers and summaries were made. The basic theory adopted is specially the work of the Argentine constitutionalist Roberto Gargarella, together with other authors. The work is divided into two chapters. The first one deals with the freedom of expression from its inception to its forecast in international treaties, especially in the American Convention. In the second chapter, then, it is proceeded the study of the sentences of the selected individual cases focused mainly on the final decision of the case and in the treatment of freedom of expression by the court.